IMPROVING READING COMPREHENSION OF THE TENTH GRADE OFFICE ADMINISTRATION STUDENTS OF SMK NEGERI 1 PINRANG BY USING EXPERIENCE-TEXT-RELATIONSHIP (ETR) METHOD - Fitriani; Nurhamdah; Ismail Latif (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2018)
The objective of the research is to find out the improvement of the student?s reading comprehension after the researcher applies Experience-Text-Relationship (ETR) Method at the tenth grade office administration students of SMK Negeri 1 Pinrang. The research design in this research was pre-experimental method with one group pre-test, treatment and post-test. The population in this research was the tenth grade students? office administration students of SMK Negeri 1 Pinrang consist of 105 students. The sample of this research was Class X Ap2 consist of 35 students. The researcher used purposive sampling because the teacher of SMK Negeri 1 Pinrang recommended this class. The researcher applies 30 items of multiple choice test. The result of this research indicated the students? mean score in pre-test is 34.54 and mean score in post-test is 87.08. It can be concluded that the rate percentage in post-test was higher than the rate percentage in pre-test in teaching reading. This showed that Experience-Text-Relationship (ETR) method can improved students? reading comprehension. Based on the result finding, the t-test was greater than the value of t-table (5.12 ? 2.021). This showed that Experience-Text-relationship (ETR) Method can improve students? reading comprehension.